Implementación de la contabilidad comercial en la empresa Ditao de la provincia de Sucumbíos en el periodo noviembre – diciembre del 2015 - Vargas Alvarado, Darwin Eduardo (2016)
DITAO owned by Mr. TarquinoIdelfonsoAñazco Ochoa, domiciled in the LagoAgrio Canton, 15-03 Manabí street and Eloy Alfaro, who is registered with the Internal Revenue Service with the RUC: No. 0700128804001 as natural person must carry accounting, its main activity is the retail of clothing. During the investigative process was implemented through the proposed objectives starting with the preparation of the inventory of assets, rights and obligations; plan and manual accounts with the verification of the supporting documents that were the basis to start the accounting records up to obtaining financial statements that provide information resources that account, the results obtained, and the inputs and outputs cash was derived. Upon completion of the investigative process it is accomplished conclude that with the development of the accounting records Financial Statements that provided information that allowed us to recommend the implementation of accounting as an effective tool to organize accounting books and to consider taking decisions as presented alternative solutions to problems and planning management investment company.